Contraceptive Use in East Timorese Ex-Refugee Women in Indonesia: Determinants and Barriers - Maria Paula Marla Nahak; Maria Lupita Nena Meo; Maria Getrida Simon (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: Poor access to contraceptive services is a global health problem, especially in the marginal community order. Refugee camps and areas with weak community order are the groups with the lowest prevalence of contra